Expressional and Prognostic Value of S100A16 in Pancreatic Cancer Via Integrated Bioinformatics Analyses - Tu, Gangping; Gao, Wenzhe; Li, Ying; Dian, Yating; Xue, Bingyang; Niu, Li; Yu, Xiao; Zhu, Hongwei (Frontiers in Cell and Developmental Biology, 2021)
Studies have shown that the calcium-binding protein family S100 may play a role in the development of pancreatic cancer (PC), but the role of S100A16 in PC is still unknown. In this study, Oncomine was first used to detect the expression level and prognosis of S100A16 in PC and other tumors. The results showed that S100A16 was highly expressed in PC tissues compared with normal pancreas, and the increased expression level may be related to poor prognosis in PC patients. The TCGA and ICGC RNA-seq data of PC patients were downloaded, and the S100A16-related differentially expressed genome (DEGs) was defined by taking the intersection of two gene sets, then GO and KEGG pathways were analyzed. Boxplot analysis of the correlation between clinical features and S100A16 expression level, the use of single factor and multi-factor survival and preliminary test the expression of Cox regression analysis the relationship between the clinical features and S100A16 situation, and further establish a risk score calculation S100A16 each patient's risk score, a multivariable Cox regression is adopted to establish the nomograph, and the model of clinical predictive value. Gene set enrichment analysis (GSEA) investigated the effect of S100A16 expression differences on downstream biological processes. Using TIMER, ImmuneCellAI and GSEA, we analyzed the correlation between S100A16 and pancreatic cancer immune infiltration, and predicted the response of patients to checkpoint Blocker (ICB) . S100A16 is involved in the occurrence and development of PC, affecting the prognosis of patients, and may have potential reference value for the immunotherapy of PC.